Development, implementation and evaluation of a health promoting school training programme for educators in high schools of Mankweng Circuit, Limpopo Province, South Africa - Mashamba, Takalani Joyce (My University, 2021)
Background: The purpose of this study was to develop, implement and evaluate a Health Promoting School (HPS) training programme for educators in the high schools of the Mankweng Circuit, Limpopo Province, South Africa. Methods: This is an explanatory mixed method study conducted among high school learners to identify risk behaviours, physical environmental and school climate factors to develop, implement and evaluate a Health Promoting School training programme for educators in the high schools of Mankweng Circuit. A structured questionnaire and a semi-structured interview guide were used to collect data. Quantitative data was collected from a total of (n=828) learners on risk behaviours, environmental and the school climate factors including curriculum and policy factors from (n=12) schools, while the key informants involved in decision making at the schools provided qualitative data on the same topics. The study highlighted potential areas for the initiation of Health Promoting Schools in Limpopo Province. Results: About 828 learners participated in this study, of which, 416 (50.2%) were males and 412 (49.8%) were females. More males than females indicate that they consumed alcohol (47% versus 24%, p<0.05), while 11% (90/840) of the learners report to have smoked cigarettes, a higher proportion of which are males rather than females (18% versus 4%, p<0.05). Quantitative results were further explored through analysis of the qualitative data from key informants who confirmed that the use of substances such as tobacco, alcohol and dagga (marijuana) is rife among school learners. Factors relevant to develop a training programme for educators were identified from the findings. The identified factors informed the development of the HPS training programme. Educators received training on HPS programme and the implementation was evaluated. Conclusion: The Health Promoting School (HPS) Training Programme improved the educator’s knowledge, understanding and skills of how schools can become Health Promoting Schools.
Thesis (Ph.D. (Health Sciences)) -- University of Limpopo, 2021
Keywords: Health Promoting Schools; Life orientation educators; Risk behaviours; School climate; Ethos; Health promotion; Health education; Classroom environment